2023
DOI: 10.3390/cancers15051511
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intra-Observer Agreement of PD-L1 SP142 Scoring in Breast Carcinoma—A Large Multi-Institutional International Study

Abstract: The assessment of PD-L1 expression in TNBC is a prerequisite for selecting patients for immunotherapy. The accurate assessment of PD-L1 is pivotal, but the data suggest poor reproducibility. A total of 100 core biopsies were stained using the VENTANA Roche SP142 assay, scanned and scored by 12 pathologists. Absolute agreement, consensus scoring, Cohen’s Kappa and intraclass correlation coefficient (ICC) were assessed. A second scoring round after a washout period to assess intra-observer agreement was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Fortunately, studies on BC have shown relative concordance among assays, ranging from good to excellent [9,10]. However, pathologist interpretation is also subject to inter-and intra-observer variability, with concordance ranging from poor to excellent, depending on the setting [11,12]. More significant discordance and worse reproducibility were reported among low-expressing cases with PD-L1 around the cutoff of 1% [12], which is made more challenging when attempting to assess whether immune cells are in close enough proximity to the cancer cells to warrant inclusion in scoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, studies on BC have shown relative concordance among assays, ranging from good to excellent [9,10]. However, pathologist interpretation is also subject to inter-and intra-observer variability, with concordance ranging from poor to excellent, depending on the setting [11,12]. More significant discordance and worse reproducibility were reported among low-expressing cases with PD-L1 around the cutoff of 1% [12], which is made more challenging when attempting to assess whether immune cells are in close enough proximity to the cancer cells to warrant inclusion in scoring.…”
Section: Discussionmentioning
confidence: 99%
“…However, pathologist interpretation is also subject to inter-and intra-observer variability, with concordance ranging from poor to excellent, depending on the setting [11,12]. More significant discordance and worse reproducibility were reported among low-expressing cases with PD-L1 around the cutoff of 1% [12], which is made more challenging when attempting to assess whether immune cells are in close enough proximity to the cancer cells to warrant inclusion in scoring. PD-L2 assessment may show similar susceptibility to interpretative differences, but a predictive scoring cutoff may prove less problematic to establish due to higher PD-L2 staining in cancer cells than in immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…These reproducibility studies are also very heterogeneous in terms of anti-PD-L1 IHC clones and platforms, the natures of cancers, the number of cases and pathologists, the use of physical glass slides or digital ones, the need for exact quantification of positive cells, or the use of semiquantitative scales and different statistical methods. Inter-and intra-observer reproducibility is reported with different agreements, from poor to excellent ones, but all the aforementioned methodological variations make the different studies difficult to compare [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Another potential issue in PD-L1 expression quantification could also be inter-and intra-pathologists' agreements in PD-L1 IHC quantification [3][4][5][6][7][8][9][10][11][12][13][14][15]. The evaluation of the reproducibility in assessing PD-L1 TPS and CPS using single PD-L1 IHC (S-IHC) but also using a more original dual IHC (D-IHC) method combining PD-L1 IHC with tumor nuclear marker IHC is the aim of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…PD-L1 is the only biomarker approved for ICIs in TNBC, but there are many controversies surrounded its use in clinical practice. PD-L1 exhibits dynamic expression, heterogeneous distribution within the tumor area, and questionable reproducibility, particularly when borderline values are considered (114)(115)(116).…”
Section: Pd-l1mentioning
confidence: 99%